2010
DOI: 10.1093/cvr/cvq031
|View full text |Cite
|
Sign up to set email alerts
|

An angiotensin II- and NF-κB-dependent mechanism increases connexin 43 in murine arteries targeted by renin-dependent hypertension

Abstract: In both large and small arteries, hypertension differently regulates Cx expression in SMC and EC layers. Cx43 is selectively increased in renin-dependent hypertension via an AngII activation of the extracellular signal-regulated kinase and NF-kappaB pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
87
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 49 publications
5
87
0
Order By: Relevance
“…Interestingly, the alteration of connexin expression, including Cx40, has also been associated with the development of such vascular diseases (2,6). Here, we provide direct evidence for a tight link between Cx40, Cx37, and eNOS at the intercellular junctions of endothelial cells, suggesting that an interplay exists between the alterations of connexin expression and eNOS expression/function occurring in vascular diseases, and also that eNOS function may be partly regulated by connexins, as already observed for other proteins such as calmodulin, caveolin-1, heat shock protein 90, or protein kinase B (21).…”
Section: Using Cx40mentioning
confidence: 99%
“…Interestingly, the alteration of connexin expression, including Cx40, has also been associated with the development of such vascular diseases (2,6). Here, we provide direct evidence for a tight link between Cx40, Cx37, and eNOS at the intercellular junctions of endothelial cells, suggesting that an interplay exists between the alterations of connexin expression and eNOS expression/function occurring in vascular diseases, and also that eNOS function may be partly regulated by connexins, as already observed for other proteins such as calmodulin, caveolin-1, heat shock protein 90, or protein kinase B (21).…”
Section: Using Cx40mentioning
confidence: 99%
“…5,6,8 Accordingly, the global invalidation of the Cx40 gene results in a sustained hypertension of mice, 9,10 which has been accounted for by an increase in the synthesis and release of renin, 8,11 as well as by peripheral vascular effects. 8,[11][12][13] The latter effects are associated with a decreased expression of the endothelial nitric oxide synthase (eNOS) in Cx40 null and Cx37 defective mice, 12,14 which impairs the release of NO whereby ECs usually relax the smooth muscle cells (SMCs) of arterioles. The SMC tone is further controlled by Ca 2+ signaling in ECs, which is also modulated by both Cx40 and Cx37.…”
mentioning
confidence: 99%
“…15,16 The physiological relevance of these observations is supported by the findings that the renin-dependent hypertension increases the expression of Cx40 in ECs, as well as that of Cx37 and Cx43 in SMCs, via an angiotensin II-dependent mechanism. 13 To assess the relative importance of Cx signaling on renin secretion and vasomotor function, a previous study has investigated the deletion of Cx40 in either RSCs or ECs, using the Cre-lox technology. 17 Strikingly, the mice lacking Cx40 in RSCs were different from Cx40 null mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Angelillo-Scherrer et al (5a) reported that deletion of Cx37 in mice shortened the bleeding time and increased thrombus propensity, thus providing a mechanism by which Cx37 limits thrombus propensity by downregulating platelet reactivity. Alonso et al (4) showed that Cx43 is increased in renin-dependent hypertension via ANG II activation of extracellular signal-regulated kinase and NF-B pathways. Our previous study demonstrated that Cx43 takes part in the regulation of vascular contractile responses after shock and that Rock1 has an important mediating effect in this process (35,66).…”
Section: Discussionmentioning
confidence: 99%